c - d (b, 2013)
Autobiographical reminiscences of Mophājjala Karima, 20th century Bengali poet from Bangladesh.
In Bengali.
Keywords: Karim, Mofazzal, -- 9; Poets, Bengali -- Bangladesh -- Biography; Poets, Bengali -- 20th century -- Biography; Bangladesh -- History -- Revolution, 1971.; x